From the Russian Occupation to the Reign of Alexandru D. Ghica. The Features of a Political Transition - MIHUȚ, Cosmin; PLOSCARU, Cristian (Studia Universitatis Babeș-Bolyai Historia, 2021)
The appointment of the Princes of Moldavia and Wallachia presented Russian officials with serious dilemmas, whether they were the leaders of the Empire's foreign policy or of the occupation administration. In the end, a solution was adopted – the selection of the Princes by the Porte from a short list of candidates proposed by Russia – in line with Russia's strategic interests regarding the Ottoman Empire as a whole and despite Pavel Kiselev's proposals that the occupation should be prolonged or, in a transitional phase, that the civilian administration of the Princes should operate in parallel with a Russian military administration. The selection of Alexandru Dimitrie Ghica as the main candidate for Wallachia and his rapid investiture by the Sultan have several explanations, including his political profile convenient for both Powers, his activity as minister and head of the militia, his personal relation with Pavel Kiselev and his access to the sums of money required for his investiture in Constantinople. However, his insufficient political prestige in relation to the country’s great boyar families, his image as a Prince submissive to the Russian will, skillfully used by his opponents, and the large debts he had accumulated, which he could not pay without generating several resounding financial scandals linked to the leasing of state revenues, were likely to herald the political crisis of the following years, the success of the opposition in undermining his regime and, finally, his dismissal after only eight years of rule. Article history: Received 2.11.2021; Revised 7.12.2021; Accepted 28.12.2021; Available online 13.04.2022. Rezumat: De la ocupaţia rusă la domnia lui Alexandru D. Ghica. Caracteristicile unei tranziţii politice. Desemnarea domnilor Moldovei şi Ţării Româneşti i-a pus pe oficialii ruşi în faţa unor serioase dileme, fie că este vorba de diriguitorii politicii externe a Imperiului, fie de conducătorii administraţiei de ocupaţie. În cele din urmă, a fost adoptată o soluţie – selectarea domnilor de către Poartă dintr-o listă scurtă de candidaţi propusă de Rusia – în accord cu interesele strategice ale Rusiei relative la Imperiul otoman în anbamblu şi în pofida propunerilor lui Pavel Kiselev ca ocupaţia să fie prelungită sau ca, într-o fază de tranziţie, administraţia civilă a domnilor să funcţioneze în paralel cu o administraţie militară rusească. Selectarea lui Alexandru Dimitrie Ghica drept candidat principal pentru Ţara Românească şi rapida sa învestire de către sultan au mai multe explicaţii, între care profilul său politic convenabil pentru ambele Puteri, activitatea sa ca ministru şi şef al miliţiei pământene, relaţia personală cu Pavel Kiselev şi accesul la sumele de bani necesare cheltuielilor impuse de învestirea sa la Constantinopol. Cu toate acestea, prestigiul politic insuficient de pronunţat în raport cu marile familii boiereşti din ţară, imaginea sa de principe supus voinţei ruseşti, abil utilizată de adversari, şi marile datorii acumulate, pe care nu le-a putut plăti fără să genereze câteva răsunătoare scandaluri financiare legate de arendarea veniturilor statului au fost de natură a anunţa criza politică din anii următori, succesul opoziţiei în a-i submina regimul şi, în cele din urmă, destituirea sa după doar opt ani de domnie. Cuvinte cheie: Regimul regulamentar, Pavel Kiselev, investitură domnească, Alexandru Dimitrie Ghica, datorii financiare